The Modernist Bestiary Translating Animals and the Arts through Guillaume Apollinaire, Raoul Dufy and Graham Sutherland - Kay, Sarah; Mathews, Timothy (Comparative Literature and Culture, 2020)
The Modernist Bestiary centres on Le Bestiaire ou Cortège d'Orphée (1911), a multimedia collaborative work by French-Polish poet Guillaume Apollinaire and French artist Raoul Dufy, and its homonym, The Bestiary or Procession of Orpheus (1979), by British artist Graham Sutherland. Rather than reconstructing the lineage of these two compositions, the book uncovers the aesthetic and intellectual processes involved that operate in different times, places and media. The Apollinaire and Dufy Bestiary is an open-ended collaboration, a feature that Sutherland develops in his re-visiting, and this book shows how these neglected works are caught up in many-faceted networks of traditions and genres. These include Orphic poetry from the past, contemporary musical settings, and bestiary writing from its origins to the present. The nature of productive dialogue between thought and art, and the refracted light they throw on each other are explored in each of the pieces in the book, and the aesthetic experience emerges as generative rather than reductive or complacent. The contributors' encounters with these works take the form of poetry and essays, all moving freely between different disciplines and practices, humanistic and posthumanist critical dimensions, as well as different animals and art forms. They draw on disciplines ranging from music, art history, translation, Classical poetry and French poetry, and are nurtured by approaches including phenomenology, cultural studies, sound studies, and critical animal studies. Collectively the book shows that the aesthetic encounter, by nature affective, is by nature also interdisciplinary and motivating, and that it spurs the critical in addressing the complex issues of 'humananimality'. 'Enacting in multiple compelling ways the mobility and relationality at the heart of its concerns, this collection makes a major contribution to the various fields into which it intervenes, including modernist studies, translation studies, critical animal studies, and research into intermedial transmission, especially between text and image and text and music.' - Martin Crowley, University of Cambridge